Strengthening Mathematical Problem Solving Skills through Canvas- Based Virtual Class on Quadratic Functions - Chika Rahayu; Lisnani; Abdul Aziz; Sugeng Sutiarso; Caswita (Mathematics Education Journal, 2026)
Many students experience difficulties in learning quadratic functions, particularly in graphing and solving contextual problems due to misconceptions and reliance on procedural memorization. This study aimed to develop and evaluate a Canvas-based virtual class to support students’ mathematical problem solving skills. A development research design using the ADDIE model was employed with tenth-grade students at a senior high school in Mesuji, Indonesia. Data were collected through pre-test and post-test problem solving assessments, questionnaires, classroom observations, and semi-structured interviews. Quantitative data were analyzed using a paired-sample t-test and normalized gain (N-gain), while qualitative data were analyzed thematically. The developed virtual class achieved very valid ratings for both media (89.2) and learning materials (85.2), indicating that its interface, navigation, interactive features, and instructional content met the expected quality standards. Students also perceived the platform as practical (76.2), particularly in terms of ease of use, accessibility, and support for learning activities. Statistical analysis showed a significant improvement in students’ mathematical problem solving performance after implementation (p < 0.001), with a moderate learning gain (N-gain = 0.68). Students performed strongest in understanding problems and devising solution strategies, whereas reflective evaluation (looking back) remained the weakest stage. Overall, the findings indicate that the Canvas-based virtual class provides a valid, practical, and effective digital learning environment for enhancing students’ mathematical problem solving skills in learning quadratic functions.